Defensive medicine: It is time to finally slow down an epidemic - Vento, Sandro; Cainelli, Francesca; Vallone, Alfredo (World Journal of Clinical Cases, 2018)
Defensive medicine is widespread and practiced the world over, with serious consequences for patients, doctors, and healthcare costs. Even students and residents are exposed to defensive medicine practices and taught to take malpractice liability into consideration when making clinical decisions. Defensive medicine is generally thought to stem from physicians’ perception that they can easily be sued by patients or their relatives who seek compensation for presumed medical errors. However, in our view the growth of defensive medicine should be seen in the context of larger changes in the conception of medicine that have taken place in the last few decades, undermining the patient–physician trust, which has traditionally been the main source of professional satisfaction for physicians. These changes include the following: time directly spent with patients has been overtaken by time devoted to electronic health records and desk work; family doctors have played a progressively less central role; clinical reasoning is being replaced by guidelines and algorithms; the public at large and a number of young physicians tend to believe that medicine is a perfect science rather than an imperfect art, as it continues to be; and modern societies do not tolerate the inevitable morbidity and mortality. To finally reduce the increasing defensive behavior of doctors around the world, the decriminalization of medical errors and the assurance that they can be dealt with in civil courts or by medical organizations in all countries could help but it would not suffice. Physicians and surgeons should be allowed to spend the time they need with their patients and should give clinical reasoning the importance it deserves. The institutions should support the doctors who have experienced adverse patient events, and the media should stop reporting with excessive evidence presumed medical errors and subject physicians to “public trials” before they are eventually judged in court.
Keywords: Adverse event; Clinical reasoning; Defensive medicine; Doctor-patient relationship; Healthcare cost; Medical education; Medical error